Effect of drain‐blocking and meteorological factors on ground water table fluctuations in Kamanos mire - Ruseckas, Juozas; Grigaliūnas, Vaidotas (Journal of Environmental Engineering and Landscape Management, 2008)
The study was carried out in a raised bog located in the Kamanos state reserve in northwestern Lithuania (56°16'N, 22°39'W). The area of the raised bog is 1722 ha. To assess the effect of meteorological factors and damming of drainage ditches on the water regime of the Kamanos mire, we have analysed the water table depth fluctuations over the last 22 years in the northern part of the mire, which was drained out in 1907, and the drainage ditch was dammed in 1999. The control plots were established in the central part of the raised bog without draining activities, where Eriophorum va‐ginatum‐Sphagnum spp. communities prevail in the ground vegetation and small Scots pine trees may also be found. The results showed that, in both natural and damaged‐by‐drainage sites of the raised bog, the air moisture deficiency and the amount of precipitation had a significant effect on the fluctuation of the water table depth during the growth period (R = 0.416 ‐ 0.761 p